The synthesis of high dispersed polstyrene suspensions with narrow particle distribution by sizes - D. B. Adikanova; G. Zh. Eligbaeva; E. V. Milushkova; I. А. Gritskova; N. A. Lobanova; N. I. Prokopov; S. M. Levachev; A. E. Harlov; M. Haddazh (Тонкие химические технологии)
Polysterene suspensions with particle diameters of 0.05-0.2 microns and narrow distribution by sizes can be synthesized at polymerization of styrene in high-disperse emulsions at high temperature and low concentration of monomer in the presence of ionic surfactant. Monodisperse polymeric suspensions with a diameter of particles 0.2 microns were prepared only in the presence of water-soluble inhibitor.